Pengujian Black Box pada Fitur Pendaftaran Online RSUD Kota Bandung dengan Teknik Boundary Value Analysis - Cahya Purnama Aji; Azhar Havis; Ridwan; Piqri Nabila Mulia; Subhanjaya Angga Atmaja (Journal on Pustaka Cendekia Informatika, 2025)
Software testing is an important process in ensuring the quality and reliability of a system. This study aims to evaluate the online registration feature on the official website of the Bandung City Hospital using the Black Box Testing technique with the Boundary Value Analysis (BVA) approach. The BVA technique was chosen because it is effective in identifying software defects that may occur in input boundary values, which are often the source of critical errors in the system. Testing focused on several important inputs in the registration process, such as the population registration number (NIK), BPJS card number, and cellphone number. The test results showed that the system was able to handle most of the boundary values ​​well, but there were several inconsistencies in input validation that could result in registration failure. These findings indicate the importance of implementing systematic and in-depth testing methods to improve system reliability, especially in digital-based public services.